2019
DOI: 10.31234/osf.io/87dn9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring engagement elicited by eye contact in Human-Robot Interaction

Abstract: The present study aimed at investigating how eye contact established by a humanoid robot affects engagement in human-robot interaction (HRI). To this end, we combined explicit subjective evaluations with implicit measures, i.e. reaction times and eye tracking. More specifically, we employed a gaze cueing paradigm in HRI protocol involving the iCub robot. Critically, before moving its gaze, iCub either established eye contact or not with the user. We investigated the patterns of fixations of participants’ gaze … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Moreover, they also suggest that increased exposure to robots modulates implicit but not explicit attitudes. Such dissociation is in line with a series of studies by Kompatsiari and colleagues showing that implicit measures, such as reaction times and eye-fixations, are more sensitive to detect the effect of social cognition manipulation in robots' behavior instead of self-report measures [38,39]. Similar results have been shown by Ghiglino et al [40].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, they also suggest that increased exposure to robots modulates implicit but not explicit attitudes. Such dissociation is in line with a series of studies by Kompatsiari and colleagues showing that implicit measures, such as reaction times and eye-fixations, are more sensitive to detect the effect of social cognition manipulation in robots' behavior instead of self-report measures [38,39]. Similar results have been shown by Ghiglino et al [40].…”
Section: Discussionsupporting
confidence: 86%
“…, 2009 ; Palanica and Itier, 2012 ; decreased peak velocity: Dalmaso et al. , 2017 ; longer fixations at iCub’s face during the eye contact compared to the no eye contact condition: Kompatsiari et al. , 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kompatsiari and colleagues, using objective measures, showed that eye contact exhibited by iCub humanoid robot ( Metta et al. , 2010 ) elicited a higher degree of ‘attentional engagement’ ( Kompatsiari et al. , 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm, by encompassing an online eye contact prior to the gaze shift, challenges classical findings of screen-based paradigms that showed an automatic gaze-cueing effect elicited by counterpredictive cues (Driver et al, 1999;Friesen & Kingstone, 1998). Moreover, a similar nonpredictive gazecueing study showed that participants not only engaged in joint attention (measured by the gaze-cueing effect) merely when the robot established eye contact before shifting the gaze, but they also fixated longer on iCub's face during eye contact than during no-eye-contact gaze (Kompatsiari, Ciardo, De Tommaso, & Wykowska, 2019a). These results advanced the knowledge related to the cognitive mechanisms affected by eye contact in joint attention research, by demonstrating that eye contact has a "freezing" effect on attentional focus, resulting in longer disengagement times and thus longer time to reallocate attention.…”
Section: Joint Attention Examined With Embodied Robots and Interactivmentioning
confidence: 71%